Hepatocellular carcinoma in a sheep - Zabid Yener; Hüdaverdi Erer (Eurasian Journal of Veterinary Sciences)
Hepatocellular carcinoma, detected in a 4-years-old sheep, was described in the present study. Grossly, grayish-while coloured. 1,7x1.5x1 cm in dimensions and well circumscribed, a solitary tumor mass were seen in the diaphragmatic aspect of the right lobe of liver. Microscopically, the neoplastic cells were arranged in solid pattern. Tumour was diagnosed as solid, poorly differentiated hepatocellular carcinoma. Immunohistochemically. some tumour markers, such as carcinoembryonic antigen (CEA), alpha-letoprotein (AFP), of the intermediate filament proteins, cylokeralin, and superficial antigens of hepatitis B virus was investigated, and alpha-letoprotein (AFP) was founded to be positive.